Regulation of lung development and regeneration by the vascular system - Woik, Nicole; Kroll, Jens (Cellular and molecular life sciences, 2015)
Blood vessels have been described a long time ago as passive circuits providing sufficient blood supply to ensure proper distribution of oxygen and nutrition. Blood vessels are mainly formed during embryonic development and in the early postnatal period. In the adult, blood vessels are quiescent, but can be activated and subsequently induced under pathophysiological conditions, such as ischemia and tumor growth. Surprisingly, recent data have suggested an active function for blood vessels, named angiocrine signaling, releasing trophogens which regulate organ development and organ regeneration including in the pancreas, lung, tumor cells, liver and bone. Lung development is driven by hypoxia as well as an intense endothelial-epithelial interaction, and important mechanisms contributing to these processes have recently been identified. This review aims to summarize recent developments and concepts about embryonic pulmonary vascular development and lung regeneration. We discuss hypoxia-inducible factor HIF-2α and vascular endothelial growth factor VEGF as important mediators in lung development and focus on endothelial-epithelial interactions and angiocrine signaling mechanisms.
Gesehen am 15.03.2018